Digital customer service : transforming customer experience for an on-screen world - DeLisi, Rick; Michaeli, Dan (John Wiley & Sons, Inc., 2021)
"This book describes how the digital transformation of Customer Service at both an operational and cultural level is happening at some companies right now--and why customers love it. Digital customer service is turning out to be easier, more cost-effective, and more personally rewarding than most would have expected--even within legacy companies that were founded 50 or 100 years ago. Digital Customer Service explains how every service interaction can and should happen right on the customer's own screen?any screen?including phone calls, chat, and self-service. The transformational result is happier customers, lower customer service costs, and higher profit. This book provides leaders in Customer Service, Customer Experience, and other customer-facing functions with new tools, frameworks, and guidance that will help them serve their customers in ways that are fundamentally different. As people have become increasingly digital-first in the way they live, so must the companies who serve them."--